Jawade Hafidz Arsyad's Perspective on Corruption in the Perspective of State Administrative Law - Ihwan, Miftakhul (Law Research Review Quarterly, 2019)
The government with all its tools as the main pillars of state administrators is increasingly faced with several problems. There needs to be unity between government elements in solving a problem, one of which is corruption, corruption is generally carried out by people who have power in a position, so that the characteristics of corruption crimes are always related to the misuse of organized power. in looking at corruption belonging to organized crime. The task of the State Administration in the welfare state according to Lemaire is mentioned as the bestuurzorg task and its function is to carry out public welfare. To achieve the goals of the state various supporting facilities are needed, in this case one of them is a legal means. The strategy offered in the perspective of State Administrative Law is to eradicate corruption, namely Public Service Bureaucracy Reform and Accountability, Eligible General Principles of Government, Good Govermance, and Eradication of the End of Corruption in a State Administrative Law Perspective.